Comparative study of life cycle cost and pavement performance on road rehabilitation methods - Ayob, Mohd Fairullazi; Ali, Maisarah (2015)
The Malaysian government has spent a large amount of money to keep maintaining the quality of Federal roads in Malaysia. In the face of high cost of road maintenance, increasing demands of road users, changing volume of traffic condition, in company with scarce of funds and limited budget allocated, the clients, including the government and private investors, are looking for the most appropriate road rehabilitation method, which able to produce high-quality pavement performance and facilitate them to achieve potential cost saving and the best value for money. The reconstruction work is a conventional method that usually applied to rehabilitate flexible pavement. The cold-in-place recycling (CIPR) is an alternative method, which has been employed in many countries worldwide, including Malaysia to rehabilitate flexible pavement. The objective of this paper is to present the outcomes of the comparative study of life cycle cost and pavement performance between two exclusive alternatives of road rehabilitation, i.e. cold-in-place recycling (CIPR) and reconstruction. The life cycle cost and performance of the flexible pavement, which has been rehabilitated using the CIPR and reconstruction methods were evaluated to identify the correlation between the costs incurred against the performance gained. Theoretically a high strength pavement should be able to sustain longer life. The results have established that the total cost of the reconstruction method is cheaper than the CIPR. However, looking at the performance of the flexible pavement, the CIPR method is superior to the reconstruction method for both the functional and structural strength performance.